Strategies for Improving the Quality of Healthcare Services through Patient Safety in Hospitals: Literature Review - Berliana Oktavia Setyawati; Setya Haksama (Lambung Mangkurat University, 2025)
Patient safety is widely regarded as the foremost priority in healthcare services, as it is essential to ensure that patients receive care that minimizes harm and maximizes positive health outcomes. The goal of improving patient safety is not only to reduce the frequency of errors during nursing care but also to significantly lower the risk of harm that may result from negligence or systemic faults within healthcare systems. In this context, effective patient safety improvement strategies are crucial for maintaining a high standard of care. This article aims to explore various strategies that hospitals can implement to enhance patient safety and, consequently, improve the overall quality of healthcare services they provide. The study employs a comprehensive literature review methodology, drawing from two major academic databases, PubMed and ScienceDirect, for articles published between 2021-2025. By applying the PRISMA method, the review process successfully identified eight articles that met the specified inclusion criteria. The results of the studies reviewed indicate several key strategies for improving healthcare quality through patient safety. These include building a strong patient safety culture, promoting complete and timely incident reporting, developing and adhering to standard operating procedures (SOPs), using structured safety checklists, and enhancing teamwork and communication (standardized handoffs).